A Linguacultural Dimensions in the Translation of Khaled Hosseini’s Narratives - Islam, A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article examines the linguacultural challenges involved in translating Khaled Hosseini’s literary works, specifically “The Kite Runner”, “A Thousand Splendid Suns”, “And the Mountains Echoed”. These novels, deeply embedded in Afghan and American cultural contexts, are characterized by rich linguistic and cultural elements such as realia, idiomatic expressions, code-switching, and culturally specific references. Translating these features into Russian and Kazakh presents significant challenges, requiring a balanced approach to preserve the authenticity and thematic depth of the narratives. The translation analysis is based on linguacultural approach, drawing on the linguistic theory of translation and the cultural turn in translation studies. This dual framework allows for a detailed analysis of foreignization and domestication strategies employed in the target texts. The findings highlight the crucial role of culturally sensitive translation in maintaining the integrity of the source text and identify the effective translation practices for multicultural literature advancing the development of literary translation. Its practical implications extend to enhancing cross-cultural dialogue, fostering global empathy, and refining translation strategies within multicultural literary contexts.